Influence of seasonal changes in daily activity and annual life cycle of Geotrigona mombuca (Hymenoptera, Apidae) in a Cerrado habitat, São Paulo, Brazil - Gobatto, André L. [UNESP]; Knoll, Fátima do Rosário Naschenveng [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2013)
The foraging activity of Geotrigona mombuca Smith, 1863 was studied under natural conditions aiming to verify the influence of seasonal changes on daily flight activity and annual cycle of the colony. Daily flight activity was monitored for a year based on the observation and counting of foragers leaving and entering the hive, as well as the kind of material transported and meteorological factors such as day time, temperature and relative humidity. The influence of seasonal changes was evidenced by alterations on daily rhythm of flight activity and by differences on transportation of food resources, building material and garbage. These data indicate that forager behavior is related to daily microclimate conditions and it is synchronized with the requirements of colony annual cycle, which determines an intense pollen collection in the summer. Thus, the recomposition of the intranidal population in spring and summer can be ensured, which is characterized both for a higher intensity of flight activity and increase in garbage and resin transport, as well as the swarming process in the spring. In this way, an action targeting the preservation or management of the species in a natural environment should consider that survival and reproduction of the colony depends greatly on the amount of available pollen in late winter.

A atividade de forrageamento de Geotrigona mombuca Smith, 1863 foi estudada em condições naturais com o objetivo de verificar a influência das mudanças sazonais na atividade diária e no ciclo anual da colônia. A atividade diária de voo foi monitorada, durante um ano, através de contagens de campeiras observadas saindo e entrando na colmeia e o tipo de material transportado, juntamente com os fatores meteorológicos hora do dia, temperatura e umidade relativa do ar. A influência das mudanças sazonais foi constatada pela alteração do ritmo diário da atividade de voo e pelas diferenças no transporte de recursos alimentares, material de construção e de resíduos. Esses dados evidenciam que o comportamento das campeiras está relacionado às condições microclimáticas diárias e sincronizadas com as exigências do ciclo anual da colônia, o qual determina uma intensa coleta de pólen no verão, garantindo a recomposição da população intranidal na primavera e verão, caracterizada tanto pela maior intensidade de atividadede de voo como pelo aumento do transporte de resina e lixo, e enxameagem na primavera. Desse modo, ações direcionadas para a preservação da espécie em ambiente natural ou para o manejo devem considerar que a sobrevivência e reprodução da colônia depende muito da quantidade de pólen disponível no final do inverno.
Influência das mudanças sazonais na atividade diária e no ciclo de vida anual de Geotrigona mombuca (Hymenoptera, Apidae) em hábitat de cerrado, São Paulo, Brasil
Keywords: Fatores meteorológicos; atividade diária; sazonalidade; recursos florais; Meteorological factors; daily activity; seasonality; floral resources